Evaluation of the effects of particle size, duration of treatment and spore concentration on rice straw delignification using phanarochaete chrysosporium burds - Gilbuena, Arni Eguna Gambe (Quezon City College of Engineering, University of the Philippines Diliman, 2011)
The effects of culture conditions on the amounts of lignin and cellulose in rice straw inoculated with the white rot fungus, Phanerochaete chrysosporium Burds were investigated. p. chrysosporium produce lignin peroxides which undergo a series of oxidative processes that degrade lignin by cleaving its aromatic rings thus facilitating the enzymatic hydrolysis of cellulose for ethanol production. The optimal concentrations of the components of the culture medium, namely; glucose, ammonium tartrate and CaC1₂ were first determined using lignin peroxidase activity as the response variable, and the resulting optimized medium was used in the subsequent experiments. Three process parameters, namely; size of the rice straw substrate, treatment duration and spore concentration, were used as independent variables with the relative amounts of lignin and cellulose as response variables in a Box-Benkhen optimization design. Low amounts of lignin in the treated rice straw samples were observed in the small substrate size range subjected to moderate to long durations of treatment. High cellulose retention, on the other hand was observed in moderately-sized rice straw sample subjected to a moderate duration of treatment and initially inoculated with a moderate P. chrysosporium spore concentration. The culture conditions which were predicted to result in the lowest amount of lignin (58.24%) with the highest amount of cellulose retained (86.14%) were substrate size of 320 µm, treatment duration of 12 days and an initial spore concentration of 1.8 x 10⁶ spores/ml of culture medium. These parameter values were used in verification experiments where the amount of lignin measured was 67.94% while that of cellulose was 83.28%. The results reported herein may be used in the design of a delignification system as a mild alternative to harsh thermo-chemical pre-treatment processes for lignocellulosic ethanol production.
Thesis (M.S. Energy Engineering)--University of the Philippines, Diliman.
Keywords: Lignin; Phlebiopsis gigantea; Phanerochaete chrysosporium